Common hand and finger injuries - Draper, R. (NCAFP Sports Medicine for the Active Patient, August 8, 2020, 2020)
Injuries to be discussed in this presentation: •Nail bed injuries •Jersey finger •Mallet finger• PIP dislocation •Boutonniere deformity •Gamekeeper`s thumb •MCP dislocations •Phalanx fractures •Metacarpal fractures